How to pack for the end of the world - Falkoff, Michelle (HarperTeen, 2020)
The Breakfast Club meets We Are the Ants in this timely story for a generation of young activists. If you knew the world was going to end tomorrow, what would you do? This is the question that haunts Amina as she watches new and horrible stories of discord and crisis flash across the news every day. But when she starts at prestigious Gardner Academy, Amina finds a group of like-minded peers to join forces with-fast friends who dedicate their year to learning survival skills from each other, before it's too late. Still, as their prepper knowledge multiplies, so do their regular high school problems, from relationship drama to family issues to friend blow-ups. Juggling the two parts of their lives forces Amina to ask another vital question: Is it worth living in the hypothetical future if it's at the expense of your actual present?